Oxygen desaturation index as alternative parameter in screening patients with severe obstructive sleep apnea - Varghese, Lalee; Rebekah, Grace; Priya N, Priya; Oliver, Ashwin; Kurien, Regi (Sleep Science, 2022)
Objectives Assess reliability of oxygen desaturation index (ODI) as an alternative parameter to apnea hypopnea index (AHI) in screening patients with severe obstructive sleep apnea (OSA).Material and Methods Retrospectively two-year data on demography, anthropometric features, polysomnography (PSG) parameters [AHI, ODI, minimum oxygen saturation (SpO2), mean SpO2], and Epworth sleepiness score (ESS) were collected and analyzed.Results Study showed significant correlation of ESS with AHI, ODI, apnea-hypopnea percentage of sleep period time (AH%SPT), mean SpO2 and minimum SpO2 with highest correlation being with AHI. A Cohen’s weighted Kappa analysis showed good concordance of 87.32% between AHI and ODI in classifying severity of OSA, with a significant R2 correlation of 0.84 on linear regression. An ODI>20 has a sensitivity of 96.6% and specificity of 69.6% in diagnosing severe OSA.Conclusion Good concordance between AHI and ODI makes nocturnal oximetry a less expensive tool to confdently screen patients with severe OSA.
Keywords: Apnea Hypopnea Index; Oxygen Desaturation Index; Obstructive Sleep Apnea; Sleepiness